Kajian Pembuatan Infused Water dari Buah Kurma (Phoenix dactylifera) dengan Penambahan Jeruk Nipis (Citrus aurantiifolia) - Murna Muzaifa; Yanti Meldasari Lubis; M. Arifullah (Jurnal Teknologi dan Industri Pertanian Indonesia, 2019)
Research has been conducted to analyze the effect of soaking time and addition of lime slices on the characteristics of infused water dates. This research was conducted in a laboratory scale using Completely Randomized Design consisting of 2 factors, namely soaking time (P) and number of lime slices (J). The first factor, soaking time consists of 3 levels, namely P1 = 1 day, P2 = 3 days, P3 = 5 days. The second factor is the number of pieces of lime (J) consisting of 3 levels, namely J1 = 1 piece, J2 = 2 pieces and J3 = 3 pieces. There were 9 treatment combinations with 3 replications, so that as a whole 27 unit experiments were obtained. The parameters analyzed were the ethanol content, Vitamin C content and hedonic test on color, aroma and taste. Ethanol content, hedonic color and aroma of infused water dates are influenced by soaking time, while the levels of Vitamin C and hedonic taste are influenced by the addition of lime. The interaction between soaking time and addition of lime influence the levels of Vitamin C of infused water. The longer soaking and the more dates used, the higher the ethanol content produced. The highest ethanol was obtained at 5 days treatment (0.98% w / v). The more the amount of lime used, the higher the levels of vitamin C in the infused water produced. The level of preference for panelists tends to decrease with increasing immersion time and addition of lime slices. Keywords :  etanol, infosed water, lime, date, Vitamin C